Perancangan Media Promosi pada Smile Island Digital Printing Menggunakan Website - Rina Dewi Indahsari; Adit Sugiarto (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2017)
Smile Island Digital Printing is a company engaged in the field of digital printing by providing solutions and consulting on various matters concerning both the world of digital printing supplies, services, machines and printing output. One of the problems faced by Smile Island Digital Printing is the promotion system that is less than the maximum thus causing no effective means of promotion, because the message is not fully accepted and impregnated by the general public. In addition, the system is less effective promotion of the impact the lack of order / order for these companies. To the authors tried to create and design a website application as a means of information and the promotion of Smile Island Digital Printing using Macromedia Dreamweaver 8, HTML programming, CSS as well as the solution of the problems Smile Island Digital Printing. This application is expected to instill a good image in the minds of the community, providing service and convenience to the consumer to see the products anytime, anywhere without having to directly come to Smile Island Digital Printing.